PENGARUH METODE BERNYANYI BERBANTU GERAK LAGU TERHADAP KEMAMPUAN MENGHAFAL KOSAKATA BAHASA ARAB PESERTA DIDIK KELAS V MIN 8 BANDAR LAMPUNG - Nabila Ulfa, Letisia; Muflihah, Intan; Basyori, Ahmad; Afif Amrullah, Muhammad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study was motivated by the low ability of students to memorize Arabic vocabulary due to the use of less engaging teaching methods. The purpose of this study was to determine the effect of the singing method assisted by song movements on students’ ability to memorize Arabic vocabulary in fifth grade at MIN 8 Bandar Lampung. This research employed a quantitative approach with a quasi-experimental design involving two groups, namely an experimental class and a control class. Data were collected through pre-test, post-test, observation, interviews, and documentation. The data were analyzed using descriptive statistics and a nonparametric hypothesis test. The results showed that the average score of vocabulary memorization ability in the experimental class was higher than that of the control class. The hypothesis testing indicated a significant difference between the two groups, which means that the singing method assisted by song movements has a significant effect on students’ ability to memorize Arabic vocabulary. In conclusion, the use of creative learning methods involving music and movement can improve students’ memory and engagement in learning Arabic.